The effect of plant density and spraying with salicylic acid on the development, harvest, and chemical components of Trigonella foenum-graecum L. seeds - Haider Sabeh Shanow Al-Jabir; Abdulla Abdulazeez Abdulla; Majid abdulhmeed Ibrahim (University of Thi-Qar Journal of agricultural research, 2024)
The investigation was carried out through the 2023-2024 growing season in one of the fields of Abi Al-Khasib District, Basrah Governorate, Iraq. The experiment aimed to study the effect of three plant densities on growing the fenugreek cv. local (61111, 81481, and 122222 ha-1) and spraying fenugreek plants with three concentrations of salicylic acid (0, 20, and 40 mg L-1) on the growth, yield, and chemical components of the seeds. The factorial investigation was taken out according to the complete randomized block design, with three replications for each treatment. The data were analyzed using the variance analysis and compared between the treatments means according to the least significant difference test at the probability level of 5%. The most important results obtained can be summarized as follows: The density of 61,111 plants ha-1 was significantly superior to the total number of leaves, the number of branches, the fresh weight of the plant, the dry weight of the plant, the total number of flowers, the number of seeds per pod, the total number of seeds, the weight of one thousand seeds, the seed yield per plant, the concentration of total soluble carbohydrates, the percentage of protein, a fat and volatile oil in the leaves reached 314.4 leaves, 17.72 branches, 48,089 g, 7.942 g, 115.22 flowers, 15.55 pod seed-1, 1430.1 seed-1, 10,694 g seed-1, 15.296 g plant-1, 76.69 mg.g-1, 10.596.41 %, %, 3.592%, respectively. This treatment showed a significant decrease in height of the plant, the day numbers to flower opening, and total seed productivity of 61.34 cm, 69.0 days, and 0.934 tons ha-1, respectively. The high density of 122,222 ha-1 plants led to a significant increase in the total seed yield, which amounted to 1.732 tons ha-1. The plants sprayed with salicylic acid at 40 mg L-1 led to significantly increased plant height, several leaves, and branches, fresh and dry weight of the plant, the total number of flowers and pods, the weight of a thousand seeds, the concentration of total soluble carbohydrates, protein, fat and volatile oil in The seeds amounted to 64.87 cm, 334.8 leaves, 17.57 branches, 48.429 g, 7.942 g, 114.67 flowers 92.22 pods, 10.55 g, 74.14 mg g-1, 23.91%, 10.529%, 3.528 %, respectively. The same concentration of salicylic acid reduced the number of days for flowers to open by 68.0 days. Whilst, the 20 mg L-1 concentration showed a significant increase in yield per plant and total productivity of 15.14 g, 1.320 tons ha-1. The relations between the two investigation factors had a significant impact on most of the recorded characteristics.